Determination of mangiferin solubility in solvents used in the biopharmaceutical industry - Jhoany Acosta; Iliana Sevilla; Suslebys Salomón; Lauro Nuevas; Aylema Romero; Daniel Amaro (GarVal Editorial Ltda., 2016)
Context: Pharmacological properties and studies of methods of extraction of mangiferin have been reported, but there are not studies related to the solubility of mangiferin in the solvents used in the pharmaceutical industry. Aims: Study the solubility of mangiferin in different solvents used in the pharmaceutical industry. Methods: The mangiferin used had a purity of 97.3% determined by High-Performance Liquid Chromatographic (HPLC), and solubility measurements were made in ethanol, methanol, water, acetone, diethyl ether, and hexane at 5, 15, 30, 40, 50 and 600C of temperature. The mangiferin concentrations were determined by ultraviolet spectrometry at 254 nm. The experimental solubility data were correlated with the Van´t Hoff equation and the dissolution heat determined. Results: The solubility of mangiferin in pure solvents decreases with increasing of temperature and in the following order: ethanol>methanol>water>diethyl ether>acetone>n hexane. Conclusions: This results indicated that mangiferin is slightly soluble in ethanol, sparingly soluble in methanol and water and practically insoluble in diethyl ether, acetone, and n-hexane.